Cooperative Learning and Achievement: Theory and Research - Slavin, Robert E.; Hurley, Eric A.; Chamberlain, Anne (Handbook of Psychology, 2003)
Slavin, Hurley, and Chamberlain present a historical review of cooperative learning. Four theoretical perspectives on cooperative learning and achievement are presented: Motivational, Social Cohesion, Cognitive Developmental, and Cognitive Elaboration Perspectives. In subsequent sections, critical philosophical differences are presented, particularly about where to locate motivation for learning behaviors, how to structure interactions among students, and how incentive and task structures impact forms of cooperative learning. In the final section, prospective areas for research are presented, and include a unified theoretical model that can guide future research efforts, inform educational practice, and foster the design of effective professional training and development.